2014
DOI: 10.1016/j.proeng.2014.12.140
|View full text |Cite
|
Sign up to set email alerts
|

CAD of Cascade Controllers for DC Drives Using Genetic Algorithm Methods

Abstract: PID controller presents the most widely used controller in industrial applications. It needs efficient methods to set-up and tune parameters of its three components based on the properties of the plant and its parameters. In this paper the cascade controller for a DC drive (consisting of the speed and current controllers in series) is designed and tuned using genetic algorithm technique with different objective functions. The method of designing two PID controllers connected in cascade by the genetic algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…GA is the oldest and most widely used metaheuristic algorithm, and it has many antecedents in the field of DC motors. This background extends to the following applications of the Genetic Algorithm: in PID controllers, to tune the parameters of DC motors when they have a time-dependent nature [38]; in the optimization of slotless BLDC motors and the effect on the distribution of magnetic flux and temperature [39,40]; to identify the dynamic state of a DC motor using the least squares error as a metric [41]; in a geared DC motor to improve the actual angular trajectory [23]; and to design a PID controller for a DC shunt motor considering a third-order model [42]. Also, the usefulness of GA for time scheduling and optimization in industrial robotized tasks has been demonstrated, improving efficiency and production time [43].…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 98%
“…GA is the oldest and most widely used metaheuristic algorithm, and it has many antecedents in the field of DC motors. This background extends to the following applications of the Genetic Algorithm: in PID controllers, to tune the parameters of DC motors when they have a time-dependent nature [38]; in the optimization of slotless BLDC motors and the effect on the distribution of magnetic flux and temperature [39,40]; to identify the dynamic state of a DC motor using the least squares error as a metric [41]; in a geared DC motor to improve the actual angular trajectory [23]; and to design a PID controller for a DC shunt motor considering a third-order model [42]. Also, the usefulness of GA for time scheduling and optimization in industrial robotized tasks has been demonstrated, improving efficiency and production time [43].…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 98%
“…It is a stochastic process in natural evolution. It have the ability to produce new individuals by changing a part of individual gene [7]. GA steps are clarified in Figure . 3.…”
Section: ) Mutationmentioning
confidence: 99%